Conflict Resolution Mechanisms in International Financial Organizations: Experiences and Collaborations in Broadening the Informal Process. Issue 3 (27th February 2014) - Nanwani, Suresh
Abstract International financial organizations (IFOs) such as the World Bank and the International Monetary Fund, and regional development banks, including the Asian Development Bank and the Inter‐American Development Bank, are covered in their charter provisions with immunity from judicial proceedings in national legal systems on employment matters. Over the years, IFOs have found a practical way to deal with employment disputes and conflict resolution. Administrative tribunals have been established to serve as judicial proceedings. Informal processes such as ombudsperson (also referred to as ombuds) services have been provided by IFOs. In recent years, growing emphasis has been placed on other informal processes such as mediation services. IFOs have collaborated with, and learned lessons from, other organizations including the United Nations, the International Ombudsman Association, multinational corporations and national agencies to improve the delivery of informal processes.